Role of Increased Sexual Activity in Expulsion of Distal Ureteral Stone Size 5 to 10 mmiIn Married Male - Sajid Mahmood Khan, Muhammad Arsalan Omer, Shams ul Islam, Asif Imran, Shafi Gahuri, Muhammad Irfan Shabbir Goraya (Pakistan Journal of Medical & Health Sciences, 2022)
Aim and Objective: To find out the role of increased sexual activity in expulsion of distal ureteral stone size 5 to 10 mm in married male. Material & Method: The study was conducted in FJMU/SGRH Lahore. 60 Married male in age range of 20-45 years were included in the study. Diabetic and hypertensive patients were excluded. The patients were divided randomly into 2 groups of 30 patients in each group. Patient in group A were advised to have sexual intercourse 3-4 times a week along with symptomatic treatment for 4 weeks. Patients in group B were advised not to have sexual activity or masturbation during the 4 weeks of study and given symptomatic treatment. alpha-blocker blocker were not used in either group. Informed consent was taken, ethical issues were taken into account. Telemedicine was utilized. Patients were instructed to pass the urine in a container, to record the stone expulsion day/week, number of pain attacks and number of analgesic injections required per week. Data regarding age, stone size, stone expulsion day/week and number of colicky attacks per week were recorded. Difference between two groups analyzed using chi-square test. P value less than 0.05 will be taken as significant. The patients whose symptoms worsened or who went into urosepsis were admitted on priority basis for ureteroscopic lithotripsy. Follow up done on weekly basis by history/examination, ultrasonography KUB, digital x-ray KUB and plain CT KUB. Results: Age range was 20-45 years in both groups. In group A stone size was 5-6.9 mm was in 14/30 patients (46.6%). 7-8.9 mm in 12/30 patients (40%) and 9-10 mm in 4/30 patients (13.3%). In group B stone size range 5-6.9 mm was in 13/30 patients (43.3%), 7-8.9 mm in 12/30 patients. (40%) in 9-10 mm in 5/30 patients (16.6%). In group A stone expulsion at the end of first two weeks was 76.6% and in 3 to 4th week it was 86.6%. in group B stone expulsion in first two weeks was 55% and 73.3% in 3rd to 4th week. In group A number of colicky attacks in first two weeks were 43.3% and in 3rd to 4th week were 23.3%. in group B number of colicky attacks in 1-2 weeks were 53.3 % and in 3 to 4 weeks were 30%. Conclusion: Married males, with distal ureteral stones (5-10mm), who practice sexual intercourse 3-4 times / week have increased stone expulsion and decreased frequency of ureteric colicks and the need for analgesia. Increased sexual activity has emerged as a new modality in MET, however further clinical trials are needed.